3D printing of polycaprolactone-based composites with diversely tunable mechanical gradients via multi-material fused deposition modeling. (February 2021) - Zhang, Xu; Wang, Jianlei; Liu, Tianxi
Abstract: The developed multi-material fused deposition modeling ( m -FDM) 3D printing approach was proposed to fabricate functionally gradient composites (FGCs) with diversely tunable mechanical gradients. The mechanical properties of the m -FDM 3D printed FGCs were studied as a whole part, including the interlaminar shear strength (ILSS), the storage modulus, and the tensile strength. The interlaminar shear testing results convinced that the loading direction plays a crucial importance in determining the overall mechanical strength. Furthermore, the FGCs with different linear continuous gradients of filler content were prepared to examine the relationship between structures and properties of the FGCs. In addition, the porosity of the m -FDM 3D printed parts was also presented to demonstrate the mechanism behind the effect of the gradient of filler content on the whole mechanical properties. Finally, a potential application as the intermediated layers between two different materials to prevent warping and spalling when heating and achieve the optimal effect of the heat and stress transfer simultaneously. The present study elaborates on the relationship between structures and properties of FGCs, which also helps to establish a theoretical foundation of the practical applications in diverse fields. Highlights: The developed multi-material fused deposition modeling 3D printing method was proposed to fabricate functionally gradient composites (FGCs) with diversely tunable mechanical gradients. The loading direction plays a key role in the interlaminar shear strength (ILSS) and storage modulus of the FGCs as an integral. The effect of the gradient of filler content on the tensile strength and the porosity of FGCs with different mechanical gradients is significant.